Genetic and Functional Characterization of a Conjugative KpVP-2-Type Virulence Plasmid From a Clinical Klebsiella pneumoniae Strain - Yang, Xuemei; Liu, Xiaoxuan; Xu, Yating; Yang, Chen; Chan, Edward Wai-Chi; Shum, Hoi-ping; Chen, Sheng (Frontiers in Microbiology, 2022)
The main mechanism of virulence in Klebsiella pneumoniae is the acquisition of K. pneumoniae virulence plasmids (KpVPs), which include two dominant types, namely, KpVP-1 (carrying iuc1, iro1, rmpA, and rmpA2) and KpVP-2 (carrying iuc2, iro2, and rmpA). Both are non-conjugative and associated with different hypervirulent clones. In contrast to KpVP-1 reported in K1, K2, and other serotypes of K. pneumoniae, KpVP-2 was only reported in K2 strains and rarely characterized. In this study, we identified a conjugative KpVP-2-type virulence plasmid from a clinical hypervirulent K. pneumoniae strain. This plasmid was generated by the integration of conjugative transfer genes into the KpVP-2-type plasmid Kp52.145 II and could be readily conjugated to Escherichia coli strain EC600 and K. pneumoniae strains of various types which are clinically existing, mediating hypervirulence. Furthermore, this kind of conjugative KpVP-2-type virulence plasmid has been disseminated in clinical settings in Hong Kong and other regions of the world. The generation of conjugative virulence plasmid may promote its transmission and explain the evolution of this type of virulence plasmid.